EVALUATION OF THE RESULTS OF JUDICIAL COMPUTER AND TECHNICAL EXPERTISES BY THE INVESTIGATORS AND THE COURT - Khаmitovnа Каdirovа Моkhigul; Kahramanovich, Abdullaev Rustam .; Anvarovich, Khujanazarov Azizjon; Ulugmurodovna, Rahimkulova Lola (International Journal of Psychosocial Rehabilitation, 2020)
Scientific and technological progress does not stand still, and today scientists and lawmakers are predicting the prospects of speedy normative consolidation of the procedure for using the latest technical developments, such as video conferencing (video communication), a strain gauge platform for assessing a person’s stressful psychophysical state, a system for conducting “electronic” criminal cases, video protocols, electronic referees and judicial expertise. Based on this, this article discusses and analyzes various aspects of the legal regulation of the use of technical and electronic means in the process of proof. In this case, the author draws attention to the types and significance of the conflict of laws governing forensic-computer expertise, including the collection, verification, and evaluation of evidence.